INFODEMIC AND THE IMPACT ON GLOBAL HEALTH - Barbosa Rocha, Diego; Cristina Condé, Renata; Rennan Soares Barbosa, Richard; Souza Santos de Sá, Daniela; Carlos Pereira de Jesus, Ely; Ferreira Silva, Laércio; Gusmão Soares, Raquel; Thereza Martins Pereira Mesquita, Maria; Ester Soares de Freitas, Maria; Kariny Soares Oliveira, Maricy; Teixeira de Freitas, Getúlio; Borges Evangelista, Christiane; et al. (Health and Society, 2026)
The present study aims to reflect on the impacts of the infodemic on global health. A theoretical-reflective study was conducted based on the concepts of health education and health promotion, that is, it proposes to think about the different dimensions that constitute it. To this end, Therrien’s proposition about the pillars that constitute an investigation phenomenon was adopted: ontology, epistemology and methodology. The search was conducted in the second half of 2024 through the guiding question: What are the impacts of the infodemic on global health? The following descriptors were used: infodemic; global health and misinformation with the help of Boolean operatives to help and refine the search for studies for analysis. The infodemic represents the phenomenon of dissemination of information, not always true, in an exacerbated way, this phenomenon can impact people’s adherence to sanitary measures, stimulate negative behavior in relation to individual and collective health, increase in the level of insecurity with the present and future, negative outcomes in relation to mental health and indiscriminate use of medications. Therefore, the performance of professionals and public managers in coping with the infodemic is essential, given the great burden of morbidity and mortality that it can cause.